2011
DOI: 10.1111/j.1462-2920.2011.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐diversity bacterial community in the gut of the fruitfly Drosophila melanogaster

Abstract: Summary The bacteria in the fruitfly Drosophila melanogaster of different life stages was quantified by 454 pyrosequencing of 16S rRNA gene amplicons. The sequence reads were dominated by 5 operational taxonomic units (OTUs) at ≤ 97% sequence identity that could be assigned to Acetobacter pomorum, A. tropicalis, Lactobacillus brevis, L. fructivorans and L. plantarum. The saturated rarefaction curves and species richness indices indicated that the sampling (85 000–159 000 reads per sample) was comprehensive. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
413
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(456 citation statements)
references
References 45 publications
39
413
1
3
Order By: Relevance
“…This contrasts with Drosophila, in which the bacterial community, at least under laboratory conditions, is rather unstable and composed of few members (Wong et al, 2011;Broderick et al, 2014). In this study, we found that the composition and richness of the gut microbial community changed markedly in BdDuox-RNAi flies.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This contrasts with Drosophila, in which the bacterial community, at least under laboratory conditions, is rather unstable and composed of few members (Wong et al, 2011;Broderick et al, 2014). In this study, we found that the composition and richness of the gut microbial community changed markedly in BdDuox-RNAi flies.…”
Section: Discussionmentioning
confidence: 46%
“…The bacterial composition of the ds-egfp-injected flies was also drastically changed from immature (5 DPR), middle age (15 DPR) and fully mature (20 DPR) B. dorsalis; the reasons might be because of the age change in the fly. In fact, the fluctuation of bacterial composition throughout adult life has been previously reported in A. gambiae and Drosophila melanogaster (Wong et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Gut microbes also play a role in invertebrate biology (Dillon and Dillon, 2003) and digestive process [Brune, 2011 [Lundgren, 2010, and recently the composition of microbe gut populations has been described in a variety of insect species, including bees (Jeyaprakash et al, 2003;Mohr and Tebbe, 2006), beetles (Egert et al, 2005;Lehman et al, 2009;Nardi et al, 2006;Zhang and Jackson, 2008), flies (Cox and Gilmore, 2007;Ren et al, 2007;Ryu et al, 2008;Shin et al, 2011;Wong et al, 2011), lepidopterans (Pauchet et al, 2010;Xiang et al, 2006) and termites (Hongoh et al, 2003). In Drosophila, the microbiome regulates host metabolic homeostatic and developmental programs by modulating the insulin/insulin-like growth factor (Shin et al, 2011).…”
Section: Microbiota: a Key Component Of Nutritional Immunologymentioning
confidence: 99%
“…The gut microbiota in these insects has been reported to include Proteobacteria (especially Acetobacteraceae and Enterobacteriaceae) and Firmicutes of the order Lactobacillales (notably Lactobacillus and Enterococcus species). Despite regional variation in conditions (pH, redox potential and so on) in the gut (Shanbhag and Tripathi, 2009), bacteria occur in the crop, midgut and hindgut, with densities up to 10 6 cells per fly (Corby-Harris et al, 2007;Cox and Gilmore, 2007;Ren et al, 2007;Roh et al, 2008;Sharon et al, 2010;Chandler et al, 2011;Storelli et al, 2011;Wong et al, 2011). Elimination of the gut bacteria can result in delayed larval development, altered lifespan and changes in nutrient allocation attributable to disruption in insect insulin signaling (Brummel et al, 2004;Shin et al, 2011;Storelli et al, 2011;Ridley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%